RS Aggarwal - Mathematics

Book: RS Aggarwal - Mathematics

Chapter: 10. Quadratic Equations

Subject: Maths - Class 10th

Q. No. 48 of Exercise 10F

Listen NCERT Audio Books to boost your productivity and retention power by 2X.


Solve: 3x2 + 5√5x – 10 = 0

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation


And either of their sum or difference = b


Thus the two terms are

Difference =

Product = using

Hence roots of equation are

Chapter Exercises

More Exercise Questions